Methylmercury detection in maternal blood samples by liquid chromatography with inductively coupled plasma mass spectrometry - Abedinlah, Amirah; Mohd Elias, Saliza; Praveena, Sarva Mangala; Abu Bakar, Suhaili; Rejali, Zulida; Jalaludin, Juliana (Universiti Putra Malaysia Press, 2021)
Methylmercury (MeHg) is one type of mercury (Hg) species known to be very toxic to humans, especially pregnant women and their fetuses. This study aims to obtain and validate the optimum condition of liquid chromatography with inductively coupled plasma mass spectrometry (LC-ICP-MS) to test MeHg concentration. To date, there is limited research that is focused on the maternal blood MeHg samples using LC-ICPMS in Malaysia. Before analysis, collected blood (500 µL) was placed into a 15 mL polypropylene test tube, followed by the addition of extractant solution [0.10% (v/v) HCl + 0.05% (m/v) L-cysteine + 0.10% (v/v) 2-mercaptoethanol] to the sample and sonicated for 15 minutes. The MeHg level was detected from the sample solution using the LC with Zorbax Eclipse XDB-C18 (4.6 x 12.5 mm, 5 µm) (Agilent Technologies) guard column and analytical column (4.6 x 150 mm, 5 µm) and was quantified by using the ICP-MS. The recovery of MeHg was in the range of 106 to 112% with RSD of less than 10%, followed by the LOD and LOQ.